- #1

- 10

- 0

Problem 1:

log

_{3}(x-1)^2 - log

_{3}(x^2 -1) = -1 + log

_{3}(x-1)

2log

_{3}(x-1) - log

_{3}(x^2 -1) = -1 + log

_{3}(x-1)

2log

_{3}(x-1) - log

_{3}(x-1) - log

_{3}(x^2 -1) = -1

log

_{3}(x-1) - log

_{3}(x^2 -1) = -1

log

_{3}x-1/(x-1)(x+1) = -1

log

_{3}1/x+1 = -1

=3^-1 = 1/3

x = 2 <=== why does it equal two?

Problem 2:

logx^5 + log x = (log x)(2logx)

5logx + logx = 2(logx)^2

6logx = 2(logx)^2

3 = logx <=== why does it equal 3? How does it turn from 6logx to 3?

x = 10^3

Thank you!